Modelling the Inflammatory Bowel Disease Specialist Nurse Workforce Standards by Determination of Optimum Caseloads in the UK. (30th July 2018) - Leary, Alison; Mason, Isobel; Punshon, Geoffrey
Abstract: Background and Aims: Crohn's disease and ulcerative colitis are the most common forms of inflammatory bowel disease [IBD], affecting 1 in 250 of the population in the UK. It is accepted that access to a specialist nurse service improves patient experience and outcome. National Standards for the Healthcare of People Who Have Inflammatory Bowel Disease [2013] defined the number of nurse specialists required at 1.5 full time equivalent per 250000 population. The aim of this study was to determine if these standards were being met and to publish a new, robust, validated standard optimising the UK nursing workforce model. Methods: Existing national data and specific workload and service data were collected from 164 IBD specialist nurses who completed a questionnaire designed to collect information on activity and complexity of work both done and undone. Results: Data were received from all of the UK; 36% of respondents were specialist nurses in the field for 3 years or less. A higher caseload than the recommended level was reported by 63% of respondents. Unpaid overtime was regularly carried out by 84% of respondents. The IBD specialist nurse was involved in all areas of the patient pathway. Areas of work left undone were psychological interventions, prescribing medicines and physical assessments. Conclusions: Compared with other specialties, IBD specialist nurses are less experienced. It is recommended that the current standard be increased to 2.5 full time equivalent specialist nurses per 250000 patients, to mitigate the increasing complexity of the role, care and the 'rookie' factor.